(3QSGdI bhGYO GdLaQs - (3GdSfO UHZI Gddg Hf QhM Gddgs
(3ChdgG (B:s
(3GYde Cf WQjb GSJNQGL GdCTjGA ef Pdc ceG gh Mbg eNUhU HGdCfHjGA s
(3BNQgG (B:s
(3cGfJ J hVYfGgG ai GdQGHYI hGdYTQjf hbS Ydi gPG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdYGeI (B- (3GdehUd (B(300 (3L(B) s
Keywords: (3GdMQha h GdChaGbs